CRISIS MANAGEMENT SKILLS OF SCHOOL ADMINISRATORS IN HIGH SCHOOLS - Aycan ÇİÇEK SAĞLAM (Fırat University, 2019)
The purpose of this study is to identify the views of school managers, who work in the high schools of the central districts in Uşak, on crisis management skills according to some variables. The population of the research- which was conducted using the quantitative method- was composed of the 19 high schools located in the Central District of Uşak province, 86 managers working in these schools during the 2013-2014 academic year. The research sample was not composed from the related population but the questionnaire was applied to all administrators from the population of the research. The scales of 42 administrators of the distributed scales were assessed. Data were obtained from “Crisis Management Skills Scale of Elementary School Principals” which was developed by Aksu and Deveci (2009). In the analyses of research data as well as descriptive statistic, t-test, one way variance analysis (ANOVA) and Tukey significance test was used. The data was analyzed by SPSS (Statistical Package for Social Sciences) 17.0 package program. According to research findings, managers see “mostly” level enough to the school managements in the crisis management skills. According to the varying task types within the general process of crisis, comparing the executive opinions related to the crisis management skills of school management, there is a significant difference between the principals and vice directors opinions. Accordingly, at crisis management skills, principals evaluate the school management more efficient than the vice directors. Also, from this research, it has been obtained that there isn’t a “significant” difference between the vocational school managers’ and public school managers’ views, according to school types variable, and between the managers’ views which were participating in in-service training and not participating in, according to the in-service training variables.